2013
DOI: 10.4049/jimmunol.1301128
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Is Not Required for the Development of Severe Chronic Experimental Autoimmune Encephalomyelitis

Abstract: Predominance of multiple sclerosis (MS) in women, reductions of disease flares during pregnancy, and their increase in the postpartum period have suggested a hormonal influence on MS activity. The hormone prolactin (PRL) has long been debated as a potential immune-stimulating factor in several autoimmune disorders, including MS and its animal model experimental autoimmune encephalomyelitis (EAE). However, to date, no data clearly ascribe a pathogenic role to PRL in these diseases. Using PRL receptor–deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
(50 reference statements)
2
25
0
Order By: Relevance
“…In line with these data, we did not detect PRL at either mRNA or protein levels in mouse primary CD4 + T cells [35]. In human T cells, PRL has been proposed to support proliferation [36], survival [37], and to act as an autocrine factor.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with these data, we did not detect PRL at either mRNA or protein levels in mouse primary CD4 + T cells [35]. In human T cells, PRL has been proposed to support proliferation [36], survival [37], and to act as an autocrine factor.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…16 [35]. These findings appear to rule out CD4 + T cells as a possible source of local PRL that could contribute in an autocrine manner to the development of autoreactive T cell responses in EAE.…”
Section: Accepted Manuscriptmentioning
confidence: 53%
See 1 more Smart Citation
“…PRL has been proposed as an autocrine factor sustaining survival and proliferation of human T cells [35,36]. On the contrary, no Prl transcript or protein have been detected in purified CD4 + T cell cultures of mouse origin [37]. In this regard, it is important to consider that a single promoter drives Prl expression in rodents, while an additional “extra-pituitary” promoter has been described in humans [38].…”
Section: Prolactin and Central Nervous System Autoimmune Responsesmentioning
confidence: 99%
“…Others and we have recently characterized the development of chronic EAE in Prlr −/− and Prl −/− mice, elicited by immunization with MOG peptide 35–55 (MOG 35–55 ). We reported that mice lacking PRLR or PRL develop chronic EAE with a modestly but significantly delayed onset and a disease severity comparable to control mice [37]. The retardation in the presentation of clinical symptoms observed in Prlr −/− and Prl −/− mice is associated with a mild delay in the development of Th1 and Th17 autoimmune responses against myelin in draining lymph nodes [37].…”
Section: Prolactin and Central Nervous System Autoimmune Responsesmentioning
confidence: 99%